Dampak Orientasi Kewirausahaan dan Pemasaran Media Sosial terhadap Kinerja Pemasaran (Studi Empiris Pada UMKM Sub Sektor Kreatif di Kota Pontianak) - Lie Heng (LPPM Universitas Widya Dharma Pontianak, 2022)
Drawing upon the resource-based view, this research focuses on how the role of entrepreneurial orientation of creative SME entrepreneurs in Pontianak, Indonesia in improving marketing performance through the role of social media marketing. The study involved 125 creative sector SMEs. By using Structural Equation Modeling (SEM) AMOS version 24, the results of the study found that social media marketing is a mediating variable between entrepreneurial orientation and marketing performance.Keywords: entrepreneurial orientation, social media marketing, marketing performance